Do South African private equity firms with portfolio companies in the rest of Africa have better returns than the Johannesburg Stock Exchange (JSE) Top 40 index companies with operations in the rest of Africa? - Soubeiga, Eric (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.